Pengembangan E-LKS Interaktif Mata Pelajaran Bahasa Inggris dengan Menggunakan Model ADDIE di Sekolah Dasar Negeri Karawaci Baru 4 Kota Tangerang - Rosnaningsih, Asih; Ardelia, Elsa; Anggestin, Tia (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
This study aims to develop This research used Research and Development (R&D) research with the ADDIE model development framework. The research subjects were Teachers of SDN Karawaci Baru 4 Kota Tangerang. The research instruments used was a feasibility test by Experts and Questionnaire. Based on the results of the questionnaire obtained a score of 87.28% so it can be concluded that the Multimedia-based Interactive E-LKS is "very good" for increasing the creativity of Teachers at SDN Karawaci 4 Kota Tangerang, especially in English Lesson.